RECENT TRENDS IN DRUG DELIVERY BY NIOSOMES: A REVIEW - Khanam, Nazia; Sachan, Anupam K; Alam, Md. Irshad; Gangwar, Sudhir S; Sharma, Ranjana (Asian Journal of Pharmaceutical Research and Development, 2013)
Niosomes or non ionic surfactant are microscopic lamellar structures which may be unilamellar or multilamellar. These are amphiphillic in nature, hence capable of entrapping both hydrophilic and lipophilic drugs for their controlled delivery. Niosomes are formulated by hydration of the lipid by the aqueous phase which may be either single surfactant or a mixture of surfactant with cholesterol. Stability of niosomes is greater as compared with other novel drug delivery techniques. Niosomes are widely used for delivery of many drugs especially in treatment of life threatening diseases, site specific targeting can be achieved with niosomes, and they are also used in diagnostic imaging purpose. This study is based upon the recent advances by which niosomes can be formulated and their application in controlled and effective delivery of various drugs.